2004
DOI: 10.1111/j.1945-5100.2004.tb01137.x
|View full text |Cite
|
Sign up to set email alerts
|

Hydrothermal alteration in the core of the Yaxcopoil‐1 borehole, Chicxulub impact structure, Mexico

Abstract: Abstract-Petrographic, electron microprobe, and Raman spectrometric analyses of Yaxcopoil-1 core samples from the Chicxulub crater indicate that the impact generated a hydrothermal system. Relative textural and vein crosscutting relations and systematic distribution of alteration products reveal a progression of the hydrothermal event in space and time and provide constraints on the nature of the fluids. The earliest calcite, halite, and gaylussite suggest that the impactite sequence was initially permeated by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
99
2
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(105 citation statements)
references
References 37 publications
3
99
2
1
Order By: Relevance
“…7c). Zurcher et al (2003) suggested that this phase could have been chlorite that is now altered to other phyllosilicate phase(s); our XRD study failed to detect any chlorite. Microprobe analyses and SEM observations indicate that the material in such veins comprises acicular clay minerals such as saponite.…”
Section: Unitmentioning
confidence: 50%
“…7c). Zurcher et al (2003) suggested that this phase could have been chlorite that is now altered to other phyllosilicate phase(s); our XRD study failed to detect any chlorite. Microprobe analyses and SEM observations indicate that the material in such veins comprises acicular clay minerals such as saponite.…”
Section: Unitmentioning
confidence: 50%
“…Models of hydrothermal systems in impact craters imply enhanced flow in peak rings (e.g., Figure F7) (Ames et al, 2004;Zürcher and Kring, 2004;Schwenzer and Kring, 2009), and thus Site M0077 is an excellent location to investigate the hydrothermal system at Chicxulub. This line of inquiry will include petrological assessment and thermochronology, as well as X-ray diffraction (XRD), X-ray fluorescence (XRF), fluid inclusion, and stable isotope analyses to examine the alteration assemblage and characterize the composition of the hydrothermal fluids (Ames et al, 2004;Lüders and Rickers, 2004;Zürcher and Kring, 2004;Osinski et al, 2005Osinski et al, , 2013. Was hydrothermal circulation focused in specific zones, as it was in Hole Yax-1 (along faults and lithologic contacts), or was it more pervasive?…”
Section: Hydrothermal Circulationmentioning
confidence: 99%
“…Drilling recovered core from the ~800 m thick Cenozoic sequence, suevite, and underlying parautochthonous Cretaceous rocks to 1511 m below the surface (Urrutia-Fucugauchi et al, 2004b). The earliest Cenozoic sediments indicate gravity flows and resurge deposits formed part of the initial crater fill (Goto et al, 2004;Whalen et al, 2008Whalen et al, , 2013 and contain geochemical evidence for long-lasting hydrothermal venting into the ocean (Rowe et al, 2004;Zürcher and Kring, 2004). Unfortunately, its location on a steep slope meant studies of the post-impact section were plagued by coarse-grained redeposited carbonates and lithification, and the very basal Paleocene appears to be missing (Arz et al, 2004;Smit et al, 2004;Rebolledo-Vieyra and Urrutia-Fucugauchi, 2004;Whalen et al, 2013).…”
Section: Previous Drillingmentioning
confidence: 99%
See 2 more Smart Citations